2000
DOI: 10.1897/1551-5028(2000)019<0360:uafaep>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis for an Equilibrium Partitioning–based Estimator of Polynuclear Aromatic Hydrocarbon Bioaccumulation Potential in Sediments

Abstract: In regulatory evaluations of contaminated sediments, an equilibrium partitioning-based screening test called theoretical bioaccumulation potential (TBP) is often performed to estimate the probable concentrations of neutral organic contaminants that would eventually accumulate in aquatic organisms from continuous exposure to a sediment. The TBP is calculated from contaminant concentration and organic carbon content of the sediment, lipid content of target organisms, and a partition coefficient, usually the biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…The ranges of measured BSAFs for each POP and species were quite large, spanning at least an order of magnitude, consistent with results reported by many investigators 9, 10, 20, even (similar to the present study) within the same estuary 31, 32. There are numerous difficulties in estimating the mean of a ratio of random variables, and these difficulties are compounded when there is a lack of correlation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ranges of measured BSAFs for each POP and species were quite large, spanning at least an order of magnitude, consistent with results reported by many investigators 9, 10, 20, even (similar to the present study) within the same estuary 31, 32. There are numerous difficulties in estimating the mean of a ratio of random variables, and these difficulties are compounded when there is a lack of correlation.…”
Section: Discussionsupporting
confidence: 92%
“…In regulatory evaluations of contaminated sediments, BSAFs have been used to determine the theoretical bioaccumulation potential 19. However, Clarke and McFarland 20 showed that large systematic and random errors are possible in theoretical bioaccumulation potential calculations and that BSAFs contribute most to the uncertainty. Values for BSAFs are also frequently used to estimate bioaccumulation at CERCLA (Comprehensive Environmental Response, Compensation, and Liability Act) sites where little or no tissue data exist, and subsequently to calculate preliminary remedial cleanup goals for sediments.…”
Section: Introductionmentioning
confidence: 99%
“…This observed variation between individuals could be due to the differences of organisms' physiological conditions and heterogeneity of sediments [37]. Variability of lipid content has long been a concern in predicting risks associated with bioaccumulation of organic chemicals due to the hydrophobic nature of persistent organic compounds [39]. However, our study suggests that the uncertainty in measurements could also have significant impact on the prediction results.…”
Section: Discussionmentioning
confidence: 87%
“…Different degrees of uncertainty and variability of model parameters were observed between individuals. Variability of lipid content has long been a concern in predicting risks associated with bioaccumulation of organic chemicals due to the hydrophobic nature of persistent organic compounds [39]. Based on the allometric relationship listed in Hendriks et al [31], the variability of computed k d is relatively small compared with the predicted results.…”
Section: Discussionmentioning
confidence: 99%
“…Once input distributions are quantified, values for each input variable and model parameter are randomly drawn from their probability distributions using, for example, a Monte Carlo approach, preserving correlations among the inputs if applicable. The resulting combination of input values is used in the model (e.g., sediment fate and transport, contaminant flux) to generate a realization [45][46][47]. The process is repeated, while the nature of the sampling ensures that the realizations are equally probable, allowing a statistical summary of the model outputs.…”
Section: Uncertainty Modeling and Decision Making: Deterministic And mentioning
confidence: 99%